Embedding Pulmonary Rehabilitation for Chronic Obstructive Pulmonary Disease in the Home and Community Setting: A Rapid Review - de Oliveira, Túlio Medina Dutra; Pereira, Adriano Luiz; Costa, Giovani Bernardo; de Souza Mendes, Liliane P.; de Almeida, Leonardo Barbosa; Velloso, Marcelo; Malaguti, Carla (Frontiers in Rehabilitation Sciences, 2022)
This paper presents a rapid review of the literature for the components, benefits, barriers, and facilitators of pulmonary rehabilitation for chronic obstructive pulmonary disease (COPD) people in-home and community-based settings. Sixty-nine studies were included: 53 home pulmonary rehabilitation (HBPR) studies and 16 community pulmonary rehabilitation (CBPR) studies. The benefits of HBPR on exercise capacity and health-related quality of life were observed in one-group studies, studies comparing HBPR to usual care, and studies comparing to hospital-based pulmonary rehabilitation, although the benefits were less pronounced in the latter. HBPR reduced hospital admissions compared to usual care and was more cost-effective than hospital pulmonary rehabilitation. Most HBPRs were designed with low-density or customized equipment, are minimally supervised, and have a low intensity of training. Although the HBPR has flexibility and no travel burden, participants with severe disease, physical frailty, and complex comorbidities had barriers to complying with HBPR. The telerehabilitation program, a facilitator for HBPR, is feasible and safe. CBPR was offered in-person supervision, despite being limited to physical therapists in most studies. Benefits in exercise capacity were shown in almost all studies, but the improvement in health-related quality of life was controversial. Patients reported the benefits that facilities where they attended the CBPR including social support and the presence of an instructor. They also reported barriers, such as poor physical condition, transport difficulties, and family commitments. Despite the minimal infrastructure offered, HBPR and CBPR are feasible, safe, and provide clinical benefits to patients with COPD. Home and community settings are excellent opportunities to expand the offer of pulmonary rehabilitation programs, as long as they follow protocols that ensure quality and safety following current guidelines.